2012
DOI: 10.1200/jco.2011.38.3265
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Trial of Vorinostat With Idarubicin and Cytarabine for Patients With Newly Diagnosed Acute Myelogenous Leukemia or Myelodysplastic Syndrome

Abstract: A B S T R A C T PurposeTo evaluate the safety and efficacy of the combination of the histone deacetylase inhibitor vorinostat with idarubicin and ara-C (cytarabine) in patients with acute myelogenous leukemia (AML) or myelodysplastic syndrome (MDS). Patients and MethodsPatients with previously untreated AML or higher-risk MDS age 15 to 65 years with appropriate organ function and no core-binding factor abnormality were candidates. Induction therapy was vorinostat 500 mg orally three times a day (days 1 to 3), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 160 publications
(107 citation statements)
references
References 22 publications
2
103
0
2
Order By: Relevance
“…Our results indicate that HDACi target the bone marrow microenvironment in addition to directly killing AML cells, which may help explain their efficacy in AML combination therapy (11,13,14). Disordered epigenetics within AML cells originally suggested that HDACi may be useful for treating AML (40,41).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our results indicate that HDACi target the bone marrow microenvironment in addition to directly killing AML cells, which may help explain their efficacy in AML combination therapy (11,13,14). Disordered epigenetics within AML cells originally suggested that HDACi may be useful for treating AML (40,41).…”
Section: Discussionmentioning
confidence: 81%
“…These drugs globally regulate gene expression via increasing acetylation of histones, proteins that control chromatin accessibility to transcription factors. In AML, HDACi have shown efficacy in combination with standard chemotherapeutics such as cytarabine (11)(12)(13)(14) …”
mentioning
confidence: 99%
“…The combination of vorinostat with idarubicin and cytarabine had synergistic activity that was maximal when vorinostat preceded cytarabine. In a phase II trial, the response rate of 85% of the combination was superior to that of idarubicin and cytarabine alone; notably, there were responses in all patients with FLT3-ITD mutations 81,82 . Phase II trials using administration of vorinostat in refractory cutaneous T-cell lymphoma patients showed an objective response in nearly 30% of these patients 30,83 .…”
Section: Clinical Studies and Registered Drugsmentioning
confidence: 97%
“…The addition of vorinostat to standard induction therapy with cytarabine and idarubicin was recently evaluated in a phase II trial that included 68 patients with AML. The investigators found no vorinostatrelated toxicity and therefore will pursue a randomized trial investigating the efficacy of adding vorinostat to standard induction versus standard therapy alone [30].…”
Section: Epigenetic Modulatorsmentioning
confidence: 99%